A reatualização do mito grego de Orfeu por Camus - Amadio, Márcia Helena Ribeiro (2007)
The present research has as object to analyze how the greek myth Orpheus was modernized by Marcel Camus film Black Orpheus. We took the approach theoretically defined as parody, specially the carnavalesque and grotesque effects in the light of Mikhail Bakhtin in The popular culture in the Middle Ages and Renaissance - the context by Francois Rabelais and Linda Hutcheon in A Theory of Parody. Furthermore, we will mention theoretical concepts referring to myth by Mircea Eliade.